Energy Harvesting from AC Magnetic Field Using PZT Piezoelectric Cantilever Beams - Mariusz Kucharek; Bogdan Dziadak; Jacek Starzyński; Leszek Książek (Energies)
This article investigates energy harvesting methods designed to capture energy from the alternating magnetic field surrounding a current-carrying conductor. The study focuses on the use of piezoelectric transducers in both monolithic and bimorph configurations. Experimental tests were conducted using vibrating beam structures composed of a single-layer piezoelectric material as well as bimorph piezoelectric composites, both utilizing lead zirconate titanate (PZT) as the active material. The results demonstrate a significant improvement in energy harvesting efficiency when using the bimorph configuration. Specifically, the bimorph-based system generated a peak voltage of 4.26 V and a current of 127.16 μA, resulting in an RMS power output of 272.48 μW. The operating principles, signal conditioning strategies, and structural differences in the evaluated designs are discussed in detail. The outcomes indicate the potential of such systems for powering autonomous sensors in low-power industrial monitoring applications.